City management from the perspective of planning and land development - selected issues. - Sosnowski, Paweł Tomasz (The Opole Studies in Administration and Law, 2022)
The emergence and growth of cities was a consequence of the development of the society which led to increased needs and expectations of city inhabitants. They obviously varied over the centuries, but city inhabitants expected a higher standard of living. This generated the need for appropriate city management. The management and therefore the city management are defined in various ways. Irrespective of the definition, however, the city management is handled by city authorities, in particular by the executive authority. Its aim is to satisfy collective needs of the local community, i.e., to shape the living conditions meeting city inhabitants’ expectations and to improve them where they do not meet those expectations. However, the city management is not easy due to a very complex social structure. One of the instruments facilitating it is spatial planning and development. The aim of this article is to analyse how the space was shaped by city authorities and discuss the instruments with which they could and can currently shape the space and living conditions for city inhabitants.